Composite resin for restoration of a posterior tooth and polishing: clinical case report - Goyatá, Frederico dos Reis; Gontijo, Sávio Morato de Lacerda; Arruda, José Alcides Almeida de; Novaes Júnior, João Batista; Barreiros, Ivan Doche; Lanza, Célia Regina Moreira; Moreno, Amália (ARCHIVES OF HEALTH INVESTIGATION, 2019)
The aim of the present report was to describe a case of direct composite resin restoration in tooth 46, with emphasis on the importance of polishing. A 21-year-old female patient dissatisfied with the aesthetic amalgam restoration of her tooth 46 came to the our institution for correction of the situation. The procedure performed consisted of registration of occlusal contacts, selection of resin color, removal of amalgam restoration, coronal reconstruction with composite resin, occlusal adjustment, finishing and polishing, with the use of atomic force microscopy of the resin before and after polishing. A correct clinical protocol for the posterior composite resins is fundamental for the optimization of aesthetic results, for clinical performance and for consequent restorative longevity. The atomic force microscopy images of the resin used before and after polishing emphasize the necessity and clinical importance of this operative step. Descriptors: Dental Materials; Dental Restoration, Permanent; Dental Polishing; Microscopy. References Frese C, Staehle HJ, Wolff D. The assessment of dentofacial esthetics in restorative dentistry: a review of the literature. J Am Dent Assoc. 2012;143(5):461-66. Moraschini V, Fai CK, Alto RM, dos Santos GO. Amalgam and resin composite longevity of posterior restorations: A systematic review and meta-analysis. J Dent. 2015;43(9):1043-50. Kovarik RE. Restoration of posterior teeth in clinical practice: evidence base for choosing amalgam versus composite. Dent Clin North Am. 2009;53(1):71-6. Kanzow P, Wiegand A, Schwendicke F. Cost-effectiveness of repairing versus replacing composite or amalgam restorations. J Dent. 2016;54:41-7. Lynch CD, Opdam NJ, Hickel R, Brunton PA, Gurgan S, Kakaboura A, et al. Guidance on posterior resin composites: Academy of Operative Dentistry - European Section. J Dent. 2014;42(4):377-83. Fernández E, Martín J, Vildósola P, Oliveira Junior OB, Gordan V, Mjor I et al. Can repair increase the longevity of composite resins? Results of a 10-year clinical trial. J Dent. 2015;43(2):279-86. Sabbagh J, McConnell RJ, McConnell MC. Posterior composites: Update on cavities and filling techniques. J Dent. 2017;57:86-90. Constantinescu DM, Apostol DA, Picu CR, Krawczyk K, Sieberer M. Mechanical properties of epoxy nanocomposites reinforced with functionalized silica nanoparticles. Proc Struct Integ. 2017;5:647-52. Yadav RD, Raisingani D, Jindal D, Mathur R. A comparative analysis of different finishing and polishing devices on nanofilled, microfilled, and hybrid composite: a scanning electron microscopy and profilometric study. Int J Clin Pediatr Dent. 2016;9(3):201-8. Fernandes ACBCJ, Assunção IV, Borges BCD, Costa GFA. Impact of additional polishing on the roughness and surface morphology of dental composite resins. Rev Port Estomatol Med Dent Cirur Maxilofac. 2016;57(2):74-81. Antonson SA, Yazici AR, Kilinc E, Antonson DE, Hardigan PC. Comparison of different finishing/polishing systems on surface roughness and gloss of resin composites. J Dent. 2011;39(Suppl 1):e9-17. Kumari CM, Bhat KM, Bansal R. Evaluation of surface roughness of different restorative composites after polishing using atomic force microscopy. J Conserv Dent. 2016;19(1):56-62. Pimentel PEZ, Goyatá FR, Cunha LG. Influência da técnica de polimento na lisura superficial de resinas compostas. Clin int j braz dent. 2012;8(2):226-34. Chour RG, Moda A, Arora A, Arafath MY, Shetty VK, Rishal Y. Comparative evaluation of effect of different polishing systems on surface roughness of composite resin: An in vitro study. J Int Soc Prev Community Dent. 2016;6(Suppl 2):166-70. Lins FC, Ferreira RC, Silveira RR, Pereira CN, Moreira AN, Magalhaes CS. Surface roughness, microhardness, and microleakage of a silorane-based composite resin after immediate or delayed finishing/polishing. Int J Dent. 2016;2016:8346782.